2016
DOI: 10.1021/acs.orglett.5b03446
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of N-Boc-Propargylic and Allylic Amines by Reaction of Organomagnesium Reagents with N-Boc-Aminals and Their Oxidation to N-Boc-Ketimines

Abstract: Previously inaccessible N-Boc-protected propargylic and allylic amines were synthesized by the reaction between N-Boc-aminals and organomagnesium reagents through the in situ generated N-Boc-imine intermediates. The obtained N-Boc-propargylic amines could be readily converted into unprecedented N-Boc-ketimines by oxidation with manganese dioxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…White solid; mp: 76–80 °C; 15.9 mg, 65% yield. Analytical data matched previously reported values. , 1 H NMR (400 MHz, CDCl 3 ) δ 7.44–7.36 (m, 2H), 7.35–7.28 (m, 3H), 4.95–4.55 (m, 2H), 1.50–1.42 (m, 12H) ppm. 13 C NMR (101 MHz, CDCl 3 ) δ 154.9, 131.8, 128.4, 122.9, 90.0, 82.2, 80.0, 39.2, 28.5, 23.1 ppm.…”
Section: Experimental Sectionsupporting
confidence: 86%
“…White solid; mp: 76–80 °C; 15.9 mg, 65% yield. Analytical data matched previously reported values. , 1 H NMR (400 MHz, CDCl 3 ) δ 7.44–7.36 (m, 2H), 7.35–7.28 (m, 3H), 4.95–4.55 (m, 2H), 1.50–1.42 (m, 12H) ppm. 13 C NMR (101 MHz, CDCl 3 ) δ 154.9, 131.8, 128.4, 122.9, 90.0, 82.2, 80.0, 39.2, 28.5, 23.1 ppm.…”
Section: Experimental Sectionsupporting
confidence: 86%
“…Other alkyl-substituted ketimines (R 2 = methyl or isobutyl) were also applicable to this reaction (entries 7 and 8). Replacing the R 3 (Me) group on Z-ketimine 1a with a butyl, phenyl, or TIPS group, did not affect the antiand enantioselectivity (entries [9][10][11].…”
Section: Resultsmentioning
confidence: 99%
“…[3][4][5][6][7] Recently, we found that the Z isomer of ketimines can be obtained selectively by replacing one alkyl substituent with a less sterically hindered alkynyl group. 10 This type of ketimine can be considered a synthetic equivalent of the dialkylsubstituted ketimine, since the alkynyl group can be converted to an alkyl group by simple hydrogenation. Via the introduction of a chiral auxiliary to the alkynyl-substituted ketimines, the asymmetric synthesis of α-tert-amine derivatives has been realized (Scheme 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Wang and his group, 40 N-Boc aminal 62, 68 is a good choice for the synthesis of optically active propargylamine derivatives (65, 66, 67) and this was developed by Maruoka and his co-workers. 41 Less accessible N-Boc imine can be in situ obtained from more accessible N-Boc aminal under acid medium before it was made to react with various carbon nucleophile such as aldehyde 41a, b-keto ester 64, 1,3-diketones 63 having a-H atom (Scheme 25) in presence of chiral phosphoric acid catalysts (68-71, Fig.…”
Section: Metal-free Enantioselective Synthesis Of Propargylaminesmentioning
confidence: 99%